2021
DOI: 10.1007/s10995-021-03169-5
|View full text |Cite
|
Sign up to set email alerts
|

Shifting from in-person to virtual home visiting in Los Angeles County: Impact on programmatic outcomes

Abstract: Purpose This paper describes the effect that the COVID-19 pandemic, and subsequent shift from in-person to virtual (video-based) home visiting, had on the Los Angeles County Welcome Baby Home Visiting Program. Description The Welcome Baby (WB) Program is a voluntary, universal home visiting program for expectant women and women with infants in Los Angeles County implemented in 14 hospitals in Los Angeles County. Oversight of the program is managed by LA Best Babies Netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Anecdotally, study staff reported it was easier organizing visits virtually than in-person visits and participants liked the delivery mode. Similar to other home visiting programs impacted during COVID-19 (e.g., Bock et al, 2021), the opportunity suggests that virtual visits are feasible for delivery of MIHOW and should be considered in future efforts. In addition, when the group meetings for women assigned to the MIHOW group converted to a virtual format, attendance more than doubled.…”
Section: Limitationsmentioning
confidence: 76%
See 2 more Smart Citations
“…Anecdotally, study staff reported it was easier organizing visits virtually than in-person visits and participants liked the delivery mode. Similar to other home visiting programs impacted during COVID-19 (e.g., Bock et al, 2021), the opportunity suggests that virtual visits are feasible for delivery of MIHOW and should be considered in future efforts. In addition, when the group meetings for women assigned to the MIHOW group converted to a virtual format, attendance more than doubled.…”
Section: Limitationsmentioning
confidence: 76%
“…Total scores range between 0 and 30. Scores > 10 may indicate minor depressive symptomatology with scores > 13 indicating a likely depressive illness (Cox et al, 1987; Lara-Cinisomo et al, 2017). Cronbach's alphas of the scores in the current study ranged from 0.78 to 0.87.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some programs administered by public health agencies reassigned home visiting staff to COVID-related duties. Programs may have enhanced client engagement and retention by shifting from in-home to telehealth modalities (Bock et al, 2021; Williams et al, 2021), though these transitions often come with technological and logistical challenges (Marshall et al, 2020; Traube et al, 2020). Perhaps the most plausible reason for the decrease in early program dropout is the decrease in enrollments during COVID.…”
Section: Discussionmentioning
confidence: 99%
“…Families with vulnerabilities have also been disproportionately affected by the burden of the COVID‐19 pandemic which might have affected program participation (Kirby, 2020 ; Raifman & Raifman, 2020 ). On the contrary, program completion rates and adherence to requirement protocol assessments remained at high levels during the transition to virtual delivery during the pandemic for the Welcome Baby universal home‐visiting program for expectant mothers and women with infants in the Los Angeles County (Bock et al., 2021 ). However, the Welcome Baby recipients are considered low‐risk which might have contributed to high program participation both pre‐ and post‐pandemic onset (Bock et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%